2021
DOI: 10.5005/jp-journals-10078-1298
|View full text |Cite
|
Sign up to set email alerts
|

Micropulse Transscleral Cyclophotocoagulation

Abstract: A bstract How to cite this article: Abdelmassih Y, Tomey K, Khoueir Z. Micropulse Transscleral Cyclophotocoagulation. J Curr Glaucoma Pract 2021;15(1):1–7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
5
11
0
Order By: Relevance
“…In our study, no significant change was noted in central macular thickness at 3, 6, or 12 months follow-up, except in one case that developed CME, which completely resolved after 8 weeks of nonsteroidal anti-inflammatory drugs. Similar complication has been noted in various other published studies 42,43 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, no significant change was noted in central macular thickness at 3, 6, or 12 months follow-up, except in one case that developed CME, which completely resolved after 8 weeks of nonsteroidal anti-inflammatory drugs. Similar complication has been noted in various other published studies 42,43 …”
Section: Discussionsupporting
confidence: 90%
“…Similar complication has been noted in various other published studies. 42,43 Persistent inflammation ( > 1 mo) associated with decrease in visual acuity has been reported in studies done by Emmanuel et al 36,38 Mild, self-limiting uveitis was reported in 7.5% of eyes by Lee et al 44 However, in our study, we found that the inflammation resolved within 1 month of follow-up period when patients were kept on tapering dose of topical steroids.…”
Section: Discussionsupporting
confidence: 37%
“…In eyes with MK, the mean energy used was 52 joules. 10 The 3 and 9 o'clock positions were avoided for most treatments (n 5 58%). The median interval between the first CPC and onset of MK was 4 years (IQR, 2.7-7.4).…”
Section: Resultsmentioning
confidence: 98%
“…The surgical technique for CPC has been previously described. 9,10 The steps and procedures for surgery and postoperative care include using G-Probe (IRIS Medical Instruments Inc, Mountain View, CA) to operate on children under general anesthesia in an operating room under aseptic conditions with transillumination to precisely identify the location of the ciliary body. 11 The surgeon avoided 3 and 9 o'clock positions along the horizontal meridian whenever possible, as well as previous tube implants and scleral thinning sites.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, mTLT has been gradually developed into a new alternative laser modality, with the superiority of relatively fewer complications and a decent efficacy [ 2 ]. Most importantly, mTLT expands the indications of cyclophotocoagulation, and it is not only applicable in the advanced stage of glaucoma [ 3 ]. However, the efficacy and safety of mTLT varies across studies, and no relevant systematic review has been conducted.…”
Section: Introductionmentioning
confidence: 99%